PUBLIC SUPPORT FOR TIMBER HOUSING PRODUCTION IN BRAZIL - De Araujo, Victor A.; Morales, Elen A. M. [UNESP]; Cortez-Barbosa, Juliana [UNESP]; Gava, Maristela [UNESP]; Garcia, Jose N. (Univ Federal Lavras-ufla, 2019)
Using face-to-face interviews and semi-structured questionnaires with timber housing developers, this study assed the perceptions of respective industries about government stimuli and public policies towards timber construction in Brazil. Four questions were developed under qualitative aspects, which were percentually measured to enable a response comparative. Thereby, 107 of 210 companies were evaluated here. Under statistical view, this sampling revealed a margin of error acceptable and next to the ideal condition. Results suggest that current policies have been apparently restrictive. Timber house producers still are dependant on strategies for whole national segments, whose scope does not promote both local cleaner industries and those focused on sustainable solutions such as from this studied sector. Tax cuts and exemptions for greener products could be an efficient alternative to incentive this production sector, and promote these sustainable timber houses. The creation of assertive public policies could attract more investors and developers to expand this industry and other forest-timber sectors and, consequently, contribute to reduce the housing shortage in Brazil.
Keywords: Incentive; Policy; Wooden house; Sectorial survey; Interview; Timber industry